District health management cycle in Malaysia - Che Abdullah, Azreena; Esahak, Azreena; Wan, Arinah Deh Sze; Nadzari, Ezy Eriyani; Nordin, Fairuz Nadiah; Subbarao, Gunenthira Rao; Zainal Abidin, Muhammad 'Adil; Juni, Muhamad Hanafiah; Minhat, Halimatus Sakdiah (Community Health Society Malaysia, 2016)
Background: Imbalance between needs, demands and resources are commonly seen in the public sector. Management team needs to manage the available resources in the best possible way to meet the health needs. This is decided by the District Health Management Team (DHMT) in the district health. The concept of District Health Management Cycle (DHMC) was initially introduced by the World Health Organization (WHO) in its District Health Management Models as part of health sector reform initiatives. This review aim to discuss the principle and concept of DHMC in Malaysia.